SAGU DAN KEBERLANJUTAN PANGAN LOKAL - Lasamahu, Helena Griffith; Pesiwarissa, Rendy C.E (Fakultas Ilmu Sosial Ilmu Politik, 2019)
order to support local food stability. This local staple food is mainly coming under its wild habitat in the jungle. Sago palm contains so many benefits and functions to support human life, especially for Rutong people, whose activity is processing this kind of staple food. Sago palm field potential in Desa Rutong is actually better than other villages in coastal area of Ambon. Unfortunately, until today, the process of harvesting, processing and packaging this staple food is still done traditionally, while its production potential is relatively high. Sago starch which are derived from sago palm, consumed as daily staple food of local people and commercially treated to support daily income of Rutong’s sago farmer as well. This staple food is mainly become local commercial commodity with a very simple chain of trading, since this is a relatively traditionally-processed food with not much variant. The distribution is also very simple: dropped to local market majorly, and some of them are brought outside. There are some constraints for sago trading which are keeping it become traditional and local. First, limited technology of harvesting and processing sago palm, so that the production output is also limited. Second, lacking capital of the farmers, and the third one, low human resources quality so that people still can’t process sago become a highly valued food. In this case, government take the key position to cope with the problem. Regarding this issue, then, government created some policies on processing and preservating this kind of local natural source of staple food, by issuing Peraturan daerah (Perda). Perda here is to protect sago palm existence, along with the trend of sago field conversion for public development. Also, governmental food aid program (raskin) on the villages is today become more popular, and apprehensively thought it will slowly drag sago as the local staple food. The effort of preservating sago palm is the most appropriate way to keep its sustainable. And to implement this policy, it needs to be supported with people’s knowledge about the value of sago as a local ability. Results research : 1) Preservating sago at countryside Rutong can realized in better because coordination among community, government countryside, and government area. 2) Preservating myths, logos, and ethos sago are efforts realize sustainable sago.